In Ovo Injection of CHIR-99021 Promotes Feather Follicle Development via Modulating the Wnt Signaling Pathway and Transcriptome in Goose Embryos (Anser cygnoides) - Feng, Ziqiang; Gong, Haizhou; Fu, Jinhong; Xu, Xiaohui; Song, Yupu; Yan, Xiaomin; Mabrouk, Ichraf; Zhou, Yuxuan; Wang, Yudong; Fu, Xianou; Sui, Yujian; Liu, Tuoya; et al. (Frontiers in Physiology, 2022)
Feather performs important physiological functions in birds, and it is also one of the economic productions in goose farming. Understanding and modulating feather follicle development during embryogenesis are essential for bird biology and the poultry industry. CHIR-99021 is a potent Wnt/β-catenin signaling pathway activator associated with feather follicle development. In this study, goose embryos (Anser cygnoides) received an in ovo injection of CHIR-9902, which was conducted at the beginning of feather follicle development (E9). The results showed that feather growth and feather follicle development were promoted. The Wnt signaling pathway was activated by the inhibition of GSK-3β. Transcriptomic analyses showed that the transcription changes were related to translation, metabolism, energy transport, and stress in dorsal tissue of embryos that received CHIR-99021, which might be to adapt and coordinate the promoting effects of CHIR-99021 on feather follicle development. This study suggests that in ovo injection of CHIR-99021 is a potential strategy to improve feather follicle development and feather-related traits for goose farming and provides profiling of the Wnt signaling pathway and transcriptome in dorsal tissue of goose embryos for further understanding of feather follicle development.